Beacon of Hope for Age-Related Retinopathy: Antioxidative Mechanisms and Pre-Clinical Trials of Quercetin Therapy - Ning Pu; Siyu Li; Hao Wu; Na Zhao; Kexin Wang; Dong Wei; Jiale Wang; Lulu Sha; Yameng Zhao; Ye Tao; Zongming Song (Antioxidants)
Age-related retinopathy is one of the leading causes of visual impairment and irreversible blindness, characterized by progressive neuronal and myelin loss. The damages caused by oxidation contributes to the hallmarks of aging and represents fundamental components in pathological pathways that are thought to drive multiple age-related retinopathies. Quercetin (Que), a natural polyphenol abundant in vegetables, herbs, and fruits, has been extensively studied for its long-term antioxidative effects mediated through diverse mechanisms. Additionally, Que and its derivatives exhibit a broad spectrum of pharmacological characteristics in the cellular responses of age-related retinopathy induced by oxidative stress, including anti-inflammatory, anti-neovascularization, regulatory, and neuroprotective effects in autophagy and apoptosis processes. This review mainly focuses on the antioxidative mechanisms and curative effects of Que treatment for various age-related retinopathies, such as retinitis pigmentosa, diabetic retinopathy, age-related macular degeneration, and glaucoma. Furthermore, we discuss emerging technologies and methods involving Que and its derivatives in the therapeutic strategies for age-related retinopathies, highlighting their promise for clinical translation.